Legal and practical challenges facing corporate taxation in relation to electronic commercial transactions in Tanzania: A case study of Dar-es-salaam - Lovililo, Aneth (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for an award of the Degree of Master of Laws in Commercial Law (LL.M-CL) of Mzumbe University.